Burns injury characteristics and outcomes at lautoka hospital, fiji - Rahul Krishna Reddy; Arun Murari; Akhtar Ali; Ronal Kumar; Livai Lutunaika; Abhay Choudhari; Swastika Devi; Famiza Kulsum (Burns Open)
Background: Burns injury are a global public health problem and one of the leading causes of morbidity and mortality. However, there is no published literature available from Lautoka Hospital in Fiji that assessed the characteristics and outcomes of burn patients. Objective: The aim of this study was to explore sociodemographic and clinical characteristics, medical care and outcomes of burn injury patient at Lautoka Hospital in order to gain deeper insights into burns related issues and improve burns care at the hospital. Method: A retrospective cross-sectional study was conducted between January 1st 2020 and June 30th 2024 at Lautoka Hospital in Fiji. Data were analysed using SPSS version 25. The association between independent variables and outcomes was assessed using Chi-square test. Results: Study population included 267 patients predominately male (57 %). Majority of the patients (59 %) were aged below 10 years. Most of the burns occurred at home (92 %). A significant proportion of patients (64 %) had burns affecting multiple regions with the lower extremities being the most commonly affected area. Partial thickness burns were observed in 87.5 % of patients. The majority of patients (55 %) had a total body surface area (TBSA) < 10 % affected by burns. Normal saline (39 %) and Paracetamol (93 %) were most commonly used intravenous fluid and analgesic respectively. Most patients (93.5 %) underwent daily hydrotherapy while 26 % required surgical interventions. The median length of hospitalisation was 7.4 days. Wound infection occurred in 25 % of patients and the mortality rate was 10 %. Conclusion: This study provides deeper insights into burn related issues in order to reduce the incidence and morbidity of burn injury, and improve care. This study is single centred and conducted retrospectively thus limiting exploration of additional associations. A multicentred prospective study is recommended.